The contribute of using vernacular materials and techniques for sustainable building - Fernandes, Jorge Emanuel Pereira (2013)
The use of local materials and techniques is one of the main features from vernacular architecture. When compared with industrially-produced materials, vernacular materials have low environmental impacts, being an alternative for sustainable building. However, industrialization have brought new standardized materials that led to the homogenization of the different building approaches and spawned a universal architecture often with no context concerns and with significant environmental impacts. As for sustainability, vernacular materials have potential to evolve and to be adapted to contemporary needs, helping to reduce the embodied energy and environmental impacts. Therefore, this paper addresses potential advantages of using local materials and techniques in the Portuguese context. Moreover, this paper establishes a comparison between vernacular and industrially-produced at level of environmental indicators (embodied energy and global warming potencial).